The Association Between Sedentary Screen Time, Non-screen-based Sedentary Time, and Overweight in Chinese Preschool Children: A Cross-Sectional Study - Hu, Rui; Zheng, Hui; Lu, Congchao (Frontiers in Pediatrics, 2021)
Introduction: Less is known about the effects of the different domains of sedentary behaviours on healthy weight in young children. This cross-sectional study examined the association between sedentary screen time (SST), non-screen-based sedentary time (NSST), and overweight (and obesity) in Chinese preschoolers. Methods: Data were collected from the Physical Activity and Health in Tianjin Chinese Children study (PATH-CC), involving healthy children 3–6 years old and their families. Children’s overweight status was classified according to the international (IOTF) childhood BMI cut‐offs. SST and NSST were reported in min/day by parents using leisure-time sedentary behaviours questionnaire. Logistic regression models adjusted by sex, age, socioeconomic status, outdoor play, and sleep duration were used. Results: In a total of 971 children (55.4% boys), 11.8% of those were children with overweight. Generally, children spent one hour per day in SST, and one hour per day in NSST. Multiple models showed that children who spent more time in SST were more likely to be overweight [OR and 95% CI: 1.22 (1.03 to 1.45)]. No correlation between time spent on NSST and children with overweight was found (P >0.05). Conclusions: This study indicated that children who spent more time in SST were more likely to be overweight, but a null correlation between NSST and overweight was found. Longitudinal studies designed to identify associations between exposures to screen media and changes in metabolic parameters during child early years are needed.